Short- and long-term exposure to ambient air pollution and circulating biomarkers of inflammation in non-smokers: A hospital-based cohort study in South Korea. (October 2018) - Lee, Hyewon; Myung, Woojae; Jeong, Byeong-Ho; Choi, Hong; Jhun, Byung Woo; Kim, Ho
Abstract: Despite increasing epidemiological evidence of an association between air pollution and adverse health outcomes, the detailed mechanisms underlying the adverse effects of air pollution on medical conditions remain unclear. We evaluated the effects of short- and long-term exposure to ambient air pollution on key inflammatory markers in non-smoking subjects. Serum fibrinogen, C-reactive protein, ferritin, and white blood cell counts were repeatedly measured 3 times in 6589 subjects at the Samsung Medical Center (Seoul, South Korea) between 2010 and 2016. Both short- (≤8-day averages) and long-term (annual averages) exposure measures of 6 air pollutants (particles < 2.5 μm, particles < 10 μm, nitrogen dioxide, sulfur dioxide, ozone, and carbon monoxide) were estimated for each subject based on available residential addresses. Linear mixed-effects models were used to relate interquartile range increases in pollutant concentrations to inflammatory marker levels. Short-term exposure to air pollution was associated with increased fibrinogen and ferritin levels. Long-term exposure to air pollution was associated with increased fibrinogen levels and white blood cell counts. The largest short- and long-term associations were observed for ferritin in response to nitrogen dioxide exposure (1.4%, 95% confidence interval [CI] 0.3–2.5) and fibrinogen exposed to particles < 2.5 μm (3.4%, 95% CI 3.0–3.8), respectively. Significantly higher associations were observed among subjects with elevated levels of inflammatory markers (upper 25th percentile), including C-reactive protein, and those with cardiac infarction, chronic obstructive pulmonary disease, cerebral infarction, or diabetes. We found clear associations between short- and long-term exposure to air pollution and inflammatory markers, especially among vulnerable subgroups. Our findings provide evidence in support of the hypothesis that air pollution increases systemic inflammation, particularly among susceptible subgroups. Highlights: Mechanisms underlying the adverse effects of air pollution on disease are unclear. We evaluated the effects of pollution on key inflammatory markers in non-smokers. Short-term air pollution was associated with increased fibrinogen and ferritin levels. Long-term air pollution was associated with elevated fibrinogen and WBC levels. Pollutants increase systemic inflammation, especially among susceptible subgroups.